The Role of AI-Driven Technologies in Shaping Future Consumers ́ Perception of Luxury Brands - Trabulsi, Bana; Escobar Rios, Andrea; Lhotáková, Markéta, 1971-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This study explores how four criteria, AI-generated content, chatbots, transparency and trust, and ethical concerns, shape Czech Generation Z future consumers´ perceptions of luxury brands. An online survey of 209 students and recent graduates shows that: (1) about two-thirds feel that AI generated content weakens authenticity, while craftsmanship videos appear most genuine; (2) reliable, personalised chatbots boost trust and are the AI feature used most often; (3) three quarters say clear explanations of the use of AI raise confidence; and (4) 70 % worry about data privacy, a concern linked to rare AI use. Overall, Generation Z welcomes AI when it is useful and transparent but rejects it when it masks human craftsmanship or raises ethical concerns. The research integrates four theories—Technology Acceptance, S-O-R, Brand Personality, and Self-Verification. Recommendations include pairing AI with visible craftsmanship, strengthening privacy controls, and educating uncertain users.
Vedoucí práce: Andrea Escobar Rios
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses